Distribution of an analgesic palmitoylethanolamide and other N-acylethanolamines in human placental membranes - Svobodova, Alzbeta; Vrkoslav, Vladimir; Smeringaiova, Ingrida; Jirsova, Katerina (PloS one, 2023)
BACKGROUND: Human amniotic and amniochorionic membranes (AM, ACM) represent the most often used grafts accelerating wound healing. Palmitoylethanolamide, oleoylethanolamide and anandamide are endogenous bioactive lipid molecules, generally referred as N-acylethanolamines. They express analgesic, nociceptive, neuroprotective and anti-inflammatory properties. We assessed the distribution of these lipid mediators in placental tissues, as they could participate on analgesic and wound healing effect of AM/ACM grafts. METHODS: Seven placentas were collected after caesarean delivery and fresh samples of AM, ACM, placental disc, umbilical cord, umbilical serum and vernix caseosa, and decontaminated samples (antibiotic solution BASE 128) of AM and ACM have been prepared. Ultra-high-performance liquid chromatography-tandem mass spectrometry was used for N-acylethanolamines analysis. RESULTS: N-acylethanolamines were present in all studied tissues, palmitoylethanolamide being the most abundant and the anandamide the least. For palmitoylethanolamide the maximum average concentration was detected in AM (350.33 ± 239.26 ng/g), while oleoylethanolamide and anandamide were most abundant in placenta (219.08 ± 79.42 ng/g and 30.06 ± 7.77 ng/g, respectively). Low levels of N-acylethanolamines were found in serum and vernix. A significant increase in the levels of N-acylethanolamines (3.1-3.6-fold, P < 0.001) was observed in AM when the tissues were decontaminated using antibiotic solution. The increase in decontaminated ACM was not statistically significant. CONCLUSIONS: The presence of N-acylethanolamines, particularly palmitoylethanolamide in AM and ACM allows us to propose these lipid mediators as the likely factors responsible for the anti-hyperalgesic, but also anti-inflammatory and neuroprotective, effects of AM/ACM grafts in wound healing treatment. The increase of N-acylethanolamines levels in AM and ACM after tissue decontamination indicates that tissue processing is an important factor in maintaining the analgesic effect.
Keywords: Ethanolamines; ethanolaminy; placenta; ženské pohlaví; endokanabinoidy; polynenasycené alkamidy; Humans; Analgesics; Placenta; Pregnancy; Female; Endocannabinoids; analgetika; těhotenství; lidé; Polyunsaturated Alkamides